EVALUATING PRODUCT ATTRIBUTES OF QUICKSILVER’S APPAREL USING IMPORTANCE AND PERFORMANCE ANALYSIS - Pangemanan, Virgilio J. P.; Pangemanan, Sifrid S; Tumewu, Ferdinand . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Product attributes is the way to differentiating in fashion industry and can give impact to customer purchase decision. The objectives of this research are to identify the importance of Quicksilver’s apparel attributes and to identify the performance of Quicksilver’s apparel attributes based on the variables such as brand name, style, retail store, and price. This research use quantitative approach and uses primary data obtained through questionnaires and uses importance and Performance Analysis. 100 respondents are the sample size of this research. The result of this study shows that brand name and price are placed in quadrant I (high important but low performance), retail store in quadrant III (low importance and low performance), while style in quadrant IV (low importance but high performance). In connection with the fashion competition that occurs in Manado, marketers must be able to act creatively in the development. Quicksilver need to conduct further internal research, in terms of follow up the result of this research, in order to increase or maintain the importance and performance of product attributes indicators that have a high impact to the consumers purchase decision that resulting in attract the customers attention and increasing the sales.Keywords: product attributes, brand name, style, retail store, price, importance and performance analysis.